A novel variable structure based adaptive control with disturbance estimation - Delibasi, Akin; Kucukdemiral, Ibrahim B.; Cansever, Galip (IEEE, 2006)
A novel, improved adaptive control methodology equipped with variable structure controller which utilizes the disturbance estimate is proposed for the control of robot manipulators. The main property of the method is that, it does not requires for any information about the disturbances that act on the system such as bounds or limits. On the other hand, the proposed control method eliminates the drawbacks of the classical adaptive controllers such as poor transient responses and poor disturbance rejection capabilities by online disturbance estimation subsystem. Simulation results on an anthropomorphic robot manipulator which is assumed to have nine unknown parameters demonstrate that, the proposed control system can achieve favorable tracking and high disturbance rejection performance when compared with its counterparts.
Keywords: NONLINEAR-SYSTEMS; Automation & Control Systems